Aeromonas veronii infection remarkably increases expression of lysozymes in grass carp (Ctenopharyngodon idellus) and injection of lysozyme expression cassette along with QCDC adjuvant significantly upregulates immune factors and decreases cumulative mortality. (August 2022) - Chen, Pei; Jin, Duo; Yang, Shijia; Yu, Xiaojing; Yi, Ganfeng; Hu, Shengbiao; Sun, Yunjun; Hu, Yibo; Cui, Jun; Rang, Jie; Xia, Liqiu
Abstract: Aeromonas veronii AvX005 is a pathogenic bacterium with high toxicity to grass carp ( Ctenopharyngodon idellus ). The expression levels of g-type (goose-type lysozyme, Lys-g) and c-type lysozyme (chicken-type lysozyme, Lys-c) in the spleen of grass carp infected with AvX005 were significantly increased by approximately 4.5 times and 27 times, respectively. The recombinant proteins rLys-g and rLys-c produced in a recombinant expression system of Escherichia coli showed significant antibacterial activity against the pathogenic bacteria AvX005. A challenge test was conducted after rLys-g and rLys-c were expressed in grass carp L8824 liver cells, and compared with the survival rate of the control cells (46.3%), the survival rate of the experimental cells (77.6% for rLys-g and 68.6% for rLys-c) was significantly increased. Grass carp were infected with AvX005 on the second day after delivering pcDNA3.1-lys -g and pcDNA- lys-c with the Quil A/cholesterol/DDA/Carbopol (QCDC) adjuvant, and both pcDNA3.1-lys -g and pcDNA- lys-c provided 70% relative protection for grass carp. The activity of lysozyme and alkaline phosphatase in the serum of grass carp was significantly increased after injection of DNA. The expression of the immune factors IgM, C3 and IL8 in the kidney was upregulated to varying degrees for pcDNA3.1-lys -g and immune factors C3 and IgM was upregulated for pcDNA- lys-c . The results indicated that pcDNA3.1-lys -g and pcDNA- lys-c may be used as immunostimulants to protect grass carp from the pathogenic bacterium AvX005. Highlights: It's the first report about the role of grass carp lysozyme in the process of resistance to A. veronii . The protective effect of grass carp lysozyme encoding gene as immunostimulants on grass carp was initially explored.